Widespread AGN feedback in a forming brightest cluster galaxy at z = 4.1, unveiled by JWST - Saxena, Aayush; Overzier, Roderik A; Villar-Martín, Montserrat; Heckman, Tim; Roy, Namrata; Duncan, Kenneth J; Röttgering, Huub; Miley, George; Aydar, Catarina; Best, Philip; Bosman, Sarah; Cameron, Alex J; et al. (Monthly notices of the Royal Astronomical Society, 2024)
We present rest-frame optical JWST Near-infrared Spectrograph (NIRSpec) integral field unit (IFU) spectroscopy of TN J1338−1942 at z = 4.1, one of the most luminous galaxies in the early universe with powerful extended radio jets. Previous observations showed evidence for strong, large-scale outflows based on its large (∼150 kpc) halo detected in Ly α, and high-velocity [O ii] emission features detected in ground-based spectroscopy. Our NIRSpec/IFU observations spatially resolve the emission line properties across the host galaxy. We find at least five concentrations of strong line emission, coinciding with discrete continuum features previously detected in imaging from Hubble Space Telescope and JWST, over an extent of ∼2 arcsec (∼15 kpc). The spectral diagnostics unambiguously trace active galactic nuclei (AGN) activity plus interaction between the interstellar medium and the radio jet as the dominant mechanisms for the ionization state and kinematics of the gas in the system. A secondary region of very high ionization lies at roughly 5 kpc away from the nucleus, and within the context of an expanding cocoon enveloping the radio lobe, this may be explained by strong shock-ionization of the entrained gas. However, it could also signal the presence of a second obscured AGN, which may offer an explanation for an intriguing outflow feature seen perpendicular to the radio axis. The presence of a dual supermassive black holes system in this galaxy would support that large galaxies in the early Universe quickly accumulated their mass through the merging of smaller units, at the centres of large overdensities. The inferred black hole mass to stellar mass ratio of 0.01−0.1 for TNJ1338 points to a more rapid assembly of black holes compared to the stellar mass of galaxies at high redshifts, consistent with other recent observations.